IN CRITERIA FOR DETERMINING THE LEVEL OF MASTERY OF FOLK CRAFTS IN THE LESSONS OF STUDENTS IN TECHNOLOGY EDUCATION (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
this article examines the types of folk crafts, pedagogical conditions, problems and ways of solving the teaching of folk crafts in technology lessons in general education schools.